LncRNA DANCR promotes proliferation and metastasis in pancreatic cancer by regulating miRNA‐33b - Yongyun Luo; Qi Wang; Lili Teng; Jie Zhang; Jianjun Song; Wenping Bo; Di Liu; Yaqin He; Airong Tan (FEBS Open Bio)
Increasing evidence indicates that long noncoding RNAs (lncRNAs) function as important regulators in biological processes and are dysregulated in various tumors. The lncRNA DANCR functions as an oncogene in various cancers, but elucidation of its role in pancreatic cancer (PC) requires further investigation. In the current study, we demonstrate that DANCR was increased in PC tissues and cell lines. Knockdown of DANCR significantly suppressed cell proliferation, migration, and invasion and influenced the levels of epithelial‐to‐mesenchymal transition‐associated proteins, as demonstrated by the observation of enhanced E‐cadherin levels and reduced N‐cadherin levels in PC cells. In addition, we identified direct binding to the predicted miR‐33b binding site on DANCR. We also showed that there is reciprocal repression between DANCR and miR‐33b. Furthermore, a miR‐33b inhibitor partially abrogated knockdown of DANCR and caused inhibitory effects. We also demonstrated that DANCR functions as a miR‐33b sponge to positively regulate MMP16 expression in PC cells. Collectively, the data reveal that DANCR exerts its function by regulating miR‐33b/MMP16 expression, implying an important role for a lncRNA–miRNA–mRNA functional network and suggesting a novel potential therapeutic target for PC.